Maps and mapping - Taylor, Barbara 1954- (New York Kingfisher Books, 1993)
Explains what maps are and why they are used, introduces symbols found on maps, and describes how cartographers map the world. Includes related activities.
Includes index.
edited hb 2015-06-16
Keywords: Maps -- Juvenile literature; Maps